Polo inhibits progenitor self-renewal and regulates Numb asymmetry by phosphorylating Pon. - Wang, H.; Ouyang, Y.; Somers, W.G.; Chia, W.; Lu, B. (Nature, 2007)
Self-renewal and differentiation are cardinal features of stem cells. Asymmetric cell division provides one fundamental mechanism by which stem cell self-renewal and differentiation are balanced. A failure of this balance could lead to diseases such as cancer. During asymmetric division of stem cells, factors controlling their self-renewal and differentiation are unequally segregated between daughter cells. Numb is one such factor that is segregated to the differentiating daughter cell during the stem-cell-like neuroblast divisions in Drosophila melanogaster, where it inhibits self-renewal. The localization and function of Numb is cell-cycle-dependent. Here we show that Polo (ref. 13), a key cell cycle regulator, the mammalian counterparts of which have been implicated as oncogenes as well as tumour suppressors, acts as a tumour suppressor in the larval brain. Supernumerary neuroblasts are produced at the expense of neurons in polo mutants. Polo directly phosphorylates Partner of Numb (Pon, ref. 16), an adaptor protein for Numb, and this phosphorylation event is important for Pon to localize Numb. In polo mutants, the asymmetric localization of Pon, Numb and atypical protein kinase C are disrupted, whereas other polarity markers are largely unaffected. Overexpression of Numb suppresses neuroblast overproliferation caused by polo mutations, suggesting that Numb has a major role in mediating this effect of Polo. Our results reveal a biochemical link between the cell cycle and the asymmetric protein localization machinery, and indicate that Polo can inhibit progenitor self-renewal by regulating the localization and function of Numb.